Storytelling research on international visitors: Interpreting own experiences in Tokyo - Martin, D.; Woodside, Arch (Emerald Group, 2011)
Purpose – Using brand netnography (analyzing consumers' first-person on-line stories that include discussions of their product and brand use), this article aims to probe how visitors interpret the places, people, and situations that they experience while traveling in Japan. Design/methodology/approach – Through analysis of online consumer stories about their trip experiences, Heider's balance theory is applied to visitors' trip experiences. Follow-up contact with the consumers allows application of autodriving methodology to gather additional post-trip insights. Findings – The results show immediate and downstream positive and negative associations of concepts, events, and outcomes in visitors' stories. Maps of consumer stories identify kernel concepts and include descriptions of how visitors live a specific destination's unique promises (e.g. distinct cultural history). Using the kernel concepts as a basis, Holt's five-step strategy for building icons is applied to the travel destination to show how a destination can create a brand identity. Research limitations/implications – Bloggers reporting their travel experience may not be representative of the population of travelers. On the other hand, travel blogs potentially can influence trip planning by other visitors collecting travel information.Practical implications – Blog reports represent an unobtrusive method of collecting emic interpretive information from consumers. Emic reporting provides deep insights about consumers' trip interpretations. Tourism and hospitality managers can use this information to improve service experiences and design communication strategies to strengthen positive iconic imagery reported by consumers. Originality/value – Emic and etic interpretations of travel experiences create a bricolage of the travelers' experiences. Autodriving methodology is extended to tourism research to gather additional insights and to better clarify informants' interpretations. This article also expands on a revisionist proposal to Holt's five-step strategy for building destinations as iconic brands and suggestions for tourism management.